2022
DOI: 10.1007/s00394-022-03051-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of collagen peptides on exercise-induced gastrointestinal stress: a randomized, controlled trial

Abstract: Purpose We examined the effects of collagen peptides (CP) supplementation on exercise-induced gastrointestinal (GI) stress. Methods In a randomized, crossover design, 20 volunteers (16 males: $$\dot{V}$$ V ˙ O2max, 53.4 ± 5.9 ml·kg−1) completed 3 trials: a non-exercise rest trial, with no supplement (REST) and then an exercise trial with CP (10 g·day−1) or placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…On day 7, participants reported to the lab in the evening (≥ 16:00), had a venous blood and urine sample collected, consumed a telemetric temperature pill (E-celsius Performance Pill, Body Cap, France) and performed a battery of cognitive function tests. Although the timing of pill ingestion (1 – 12 h before) does not appear to interfere with the validity of the sensor [ 47 ], consistent with previous studies, we provided the pill 5–8 h before our first recording [ 46 , 48 ], to ensure passage from the stomach. These telemetric pills have been shown to have excellent reliability and validity [ 49 ] and are considered the industry standard for temperature monitoring [ 50 ].…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…On day 7, participants reported to the lab in the evening (≥ 16:00), had a venous blood and urine sample collected, consumed a telemetric temperature pill (E-celsius Performance Pill, Body Cap, France) and performed a battery of cognitive function tests. Although the timing of pill ingestion (1 – 12 h before) does not appear to interfere with the validity of the sensor [ 47 ], consistent with previous studies, we provided the pill 5–8 h before our first recording [ 46 , 48 ], to ensure passage from the stomach. These telemetric pills have been shown to have excellent reliability and validity [ 49 ] and are considered the industry standard for temperature monitoring [ 50 ].…”
Section: Methodsmentioning
confidence: 86%
“…The trial order was randomly generated using online software (Graphpad Prism, CA, US). We provided CP for 7 days as this duration of intake has previously been shown to positively influence physiological markers [ 42 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported to attenuate superoxide production in neutrophil granulocytes [81] and may decrease the synthesis of pro-inflammatory mediators while inhibiting LPS-induced cytokine production [82]. Recently, CP's potential ability to reduce endotoxemia [measured via lipopolysaccharides (LPS)] after gastrointestinal stress induced by intense aerobic exercise has been demonstrated in humans [83]. A recent review also revealed hydrolyzed CP to have possible anti-inflammatory and chondroprotective effects in patients with osteoarthritis, but considerable limitations exist due to methodological disparities [84].…”
Section: Discussionmentioning
confidence: 99%